Peran Wakaf dalam Perkembangan Ekonomi di Negara Asean - Amalia Azka (Department of Islamic Banking, Faculty of Islamic Economics and Business, UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to determine the role of waqf on economic development in ASEAN countries. The research method used is qualitative methods and data analysis techniques with inductive qualitative methods. The results of the study indicate that Waqf can also be a preferred financing instrument that can develop the economy in ASEAN countries. Fundamentally, waqf management in Malaysia, Singapore, Thailand, Indonesia and Brunei Darussalam is not much different. The five countries have increased the progress of waqf management. Waqf resources may be able to collect the community's economy and can build the people's economy and community welfare. One of them is cash waqf that can help the trading community, especially as business capital, pay work costs, prepare costs, and be used to build trading facilities with reasonable rents